Why punish perpetrators of mass atrocities? : purposes of punishment in international criminal law / edited by Florian Jessberger, Julia Geneuss. - Jessberger, Florian; Geneuss, Julia, 1979- (ASIL studies in international legal theory., 2020)
This edited volume provides, for the first time, a comprehensive account of theoretical approaches to international punishment. Its main objective is to contribute to the development of a consistent and robust theory of international criminal punishment. For this purpose, the authors - renowned scholars in the fields of criminal law, international criminal law, and philosophy of law, as well as practitioners working at different international criminal courts and tribunals - address the question of meaning and purpose of punishment in international law from various perspectives. The volume fleshes out the predominant dimensions of a theory of international punishment and highlights the differences between 'ordinary' (domestic) crime and international crimes and their respective enforcement. At the same time, throughout the volume a major focus is on the practical consequences of the different theoretical approaches, in particular for the activities of the International Criminal Court.